(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2008)
By adopting a genetic methodology, a theory of personal relations has been developed that both accounts for the worst and allows for the best in human relationships. Sartre’s method of a ’dialectical degeneration’ is employed to account for our Alienation from each other while Empathy and Sympathy are introduced to allow for the closeness of a personal rapport.